2023
DOI: 10.3390/ma16124226
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Recent Advances in Hyphenated Electrochemical Techniques for the Characterization of Electroactive Materials

Abstract: A hyphenated electrochemical technique consists of the combination of the coupling of an electrochemical technique with a non-electrochemical technique, such as spectroscopical and optical techniques, electrogravimetric techniques, and electromechanical techniques, among others. This review highlights the development of the use of this kind of technique to appreciate the useful information which can be extracted for the characterization of electroactive materials. The use of time derivatives and the acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…It was also observed that the surface corrosion of all samples caused by the acid treatment did not noticeably affect their physical properties, since there are practically no differences between the treated and untreated samples (see Figures S1–S4 and Table S1 in Supplementary Materials ). Further research on the corrosion kinetics and durability of these types of materials requires the use of coupled techniques [ 82 ] to simultaneously obtain their electromagnetic, mechanical and thermodynamic properties in order to improve their use in technological applications. The oxidation and dissolution of the zinc particles on the surface of the EVA/Zn composite caused by the acidic aqueous environment can be considered part of the accelerated corrosion tests that simulate many environmental media.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that the surface corrosion of all samples caused by the acid treatment did not noticeably affect their physical properties, since there are practically no differences between the treated and untreated samples (see Figures S1–S4 and Table S1 in Supplementary Materials ). Further research on the corrosion kinetics and durability of these types of materials requires the use of coupled techniques [ 82 ] to simultaneously obtain their electromagnetic, mechanical and thermodynamic properties in order to improve their use in technological applications. The oxidation and dissolution of the zinc particles on the surface of the EVA/Zn composite caused by the acidic aqueous environment can be considered part of the accelerated corrosion tests that simulate many environmental media.…”
Section: Discussionmentioning
confidence: 99%